THE EFFECT OF TEACHER FEEDBACK ON STUDENT SELF-ESTEEM AND ACADEMIC ENGAGEMENT IN SECONDARY EDUCATION - Haidar Bilaleya; Munirah; Nina Anis (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
Teacher feedback plays a central role in shaping students’ academic experiences, particularly during adolescence, a developmental stage marked by heightened sensitivity to evaluation and identity formation. While prior research has extensively examined the impact of feedback on academic achievement, limited attention has been given to its influence on student self-esteem and academic engagement in secondary education. This study aims to investigate the direct and indirect effects of teacher feedback on students’ self-esteem and academic engagement within a structural framework. A quantitative explanatory design was employed involving 512 secondary school students selected through stratified cluster sampling. Data were collected using validated Likert-scale instruments measuring perceived teacher feedback, self-esteem, and multidimensional academic engagement. Structural equation modeling was conducted to test hypothesized relationships among variables. Results indicate that teacher feedback significantly predicts both student self-esteem and academic engagement, with self-esteem partially mediating the relationship between feedback and engagement. The model explains a substantial proportion of variance in engagement outcomes. The findings underscore the importance of constructive and supportive feedback practices in fostering positive self-concept and sustained classroom participation. Strengthening feedback quality may therefore enhance both psychological well-being and academic involvement among secondary school students.